Effect of Lyophilization on Stability of PEG-Protein Conjugate: A Case Study with Peginterferon alfa-2b - Patel Chintan; Patel Gayatri (Universidade de São Paulo, 2023)
Abstract The purpose of the present study was to develop stable lyophilized formulation of peginterferon alfa-2b which is acquiescent to the short lyophilization process. The present study evaluates the effect of buffering components and cryoprotectant(s) on depegylation of the peginterferon alfa-2b in combination with lyophilization process. Finally, a short lyophilization process was identified which can produce a stable pharmaceutical form of peginterferon alfa-2b without any depegylation during long-term storage. Formulations were analyzed mainly for depegylation by HP-size exclusion chromatography and in-vitro antiviral activity. Residual moisture content in the lyophilized product was also used as a key indicating parameter to check its role with respect to depegylation upon storage under various temperature conditions. It was observed that the peginterferon alfa-2b when formulated in presence of cryoprotectant like sucrose requires longer lyophilization process of about 5 days, irrespective of the buffering components used, to reduce the level of residual moisture content and thereby to produce the stable formulation without depegylation. A stable formulation in presence of high concentration of lactose as a cryoprotectant was developed which can withstand stresses exerted to protein-polymer conjugate during lyophilization phases without any significant depegylation. A short lyophilization process of about 48 hours can be utilized for peginterferon alfa-2b when formulated in presence of lactose as a cryoprotectant through which a stable lyophilized formulation can be produced as against longer process required when sucrose is used a cryoprotectant, which is essential from commercial point of view as lyophilization is a costly process.